Tomographie des Schallfelds von Ultraschallwandlern mittels Schlierentechnik - Hetkämper, Tim; Dreiling, Dmitrij; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)

Rezension: Hendrik Kasten und Denis Vogel: Grundlagen der ebenen Geometrie – Eine zugängliche aber exakte Einführung in die ebene Geometrie - Hoffmann, Max (Mathematische Semesterberichte)

German university students’ views of nature of science in the introductory phase - Woitkowski, David; Rochell, Leonie; Bauer, Anna (Physical Review Physics Education Research)

HyOpt - Optimization-Based Development of Hybrid Materials - Triebus, Marcel; Tröster, Thomas (9th NRW Nano Conference - Innovations in Materials and Applications)

Providing Decision Makers with Tailored Decision Support Systems - Kirchhoff, Jonas (The 1st Early Career Researchers Workshop Co-Located with ECSS 2021)

The digital home learning environment and its relation to children’s ICT self-efficacy - Bonanati, Sabrina; Buhl, Heike M. (Learning Environments Research)
With the rapid progress of technological development, self-efficacy in reference to digital devices (i.e., information and computer technology [ICT] self-efficacy) is an important driver that helps students to deal with technological problems and support their lifelong learning processes. Schools, peers, and home learning environments are important sources for the development of positive self-efficacy. Expanding on previous research, we investigated the associations between different aspects of the digital home learning environment and students’ ICT self-efficacy. The moderation effects of gender were also tested. A total of 651 children answered a questionnaire about different digital home learning environment dimensions and estimated their ICT self-efficacy using an adapted scale—Schwarzer and Jerusalem’s (1999) general self-efficacy scale. Using the structural equation modeling technique, a digital home learning environment containing six different qualities of parental support was investigated. Families’ cultural capital, parents’ attitudes toward the Internet, and shared Internet activities at home contributed positively to ICT self-efficacy. We observed small gender differences, with the moderation effect being nonsignificant. The results help researchers and practitioners to understand how different dimensions of the digital home learning environment support ICT self-efficacy. We will discuss how parents can enhance the home learning environment and how teachers can integrate this knowledge into formal education.
Keywords: Digital media use; Gender; Home learning environment; ICT self-efcacy; Motivation; Parental involvement

Latent Congruence Model to Investigate Similarity and Accuracy in Family Members' Perception: The Challenge of Cross-National and Cross-Informant Measurement (Non)Invariance - Tagliabue, Semira; Zambelli, Michela; Sorgente, Angela; Sommer, Sabrina; Hoellger, Christian; Buhl, Heike M.; Lanz, Margherita (Frontiers in Psychology)
Several methods are available to answer questions regarding similarity and accuracy, each of which has specific properties and limitations. This study focuses on the Latent Congruence Model (LCM; Cheung, 2009), because of its capacity to deal with cross-informant measurement invariance issues. Until now, no cross-national applications of LCM are present in the literature, perhaps because of the difficulty to deal with both cross-national and cross-informant measurement issues implied by those models. This study presents a step-by-step procedure to apply LCM to dyadic cross-national research designs controlling for both cross-national and cross-informant measurement invariance. An illustrative example on parent–child support exchanges in Italy and Germany is provided. Findings help to show the different possible scenarios of partial invariance, and a discussion related to how to deal with those scenarios is provided. Future perspectives in the study of parent–child similarity and accuracy in cross-national research will be discussed.
Keywords: latent congruence model; measurement invariance; similarity; accuracy; cross-national; cross-informant; parent-child relationship; support exchanges

Intergenerational Value Similarity and Subjective Well-Being - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on the association of intergenerational value similarity and adult children’s and parents’subjective well-being, on the linkage between relationship quality and subjective well-being. Mediation effects of the relationship quality on the associations between value similarity and subjective well-being were focused. The sample consisted of 600 adult German children (53.8% women) and their parents. Dyadic correlations were constructed to determine the value similarity. In this study, the general value orientation and the family values were objects of research. We measured the subjective well-being with the Satisfaction with Life Scale and we used the Network of Relationships Inventory (NRI) to measure the relationship quality. Associations between subjective well-being and value similarity, and between subjective well-being and relationship quality, as well as mediation effects, were found. All effects depend on gender and perspective.
Keywords: adult child–parent dyads; relationship quality; life satisfaction; parent–child relationship; intergenerational stake hypothesis; mediation analyses

Augmented Reality als Experimentierhilfe bei Beobachtung und Deutung - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)
Keywords: digitale Medien

Messverfahren für die akustische Absorption in reinen Fluiden zur Bestimmung der Volumenviskosität - Claes, Leander
Die vollständige Beschreibung fluiddynamischer und akustischer Vorgänge setzt voraus, dass die Eigenschaften des Fluids hinlänglich bekannt sind.Während Fluidkenngrößen, wie etwa die Schallgeschwindigkeit oder die Scherviskosität, für viele Flüssigkeiten über weite Bereiche des thermodynamischen Zustandsraums bekannt sind, existieren für die Volumenviskosität nur eine geringe Anzahl Messdaten.In dieser Arbeit wird daher ein Messverfahren zur selektiven Bestimmung der Volumenviskosität von Flüssigkeiten, basierend auf der Absorption von Ultraschallwellen, entwickelt und realisiert.Schwerpunkte bilden dabei der simulationsgestützte Entwurf von Algorithmen zur Auswertung der Messsignale sowie die Analyse und Weiterentwicklung einer Messanordnung, basierend auf dem Puls-Echo-Verfahren. Neben der Absorption im Fluid treten dabei weitere Effekte (zum Beispiel Beugung oder unvollständige Reflexion) auf, die das akustische Signal schwächen oder anderweitig beeinflussen. Die Entwicklung von Verfahren zur Trennung dieser Effekte von der akustischen Absorption bildet daher einen weiteren Schwerpunkt dieser Arbeit.Abschließend wird die Volumenviskosität aus der gemessenen akustischen Absorption für unterschiedliche Fluide in verschiedenen thermodynamischen Zuständen unter Zuhilfenahme anderer bekannter Fluidkenngrößen bestimmt sowie eine Unsicherheitsbetrachtung durchgeführt.

Spectral Asymptotics for Kinetic Brownian Motion on Surfaces of Constant Curvature - Kolb, Martin; Weich, Tobias; Wolf, Lasse (Annales Henri Poincaré)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold M is a stochastic process that models a random perturbation of the geodesic flow. If M is an orientable compact constantly curved surface, we show that in the limit of infinitely large perturbation the L2-spectrum of the infinitesimal generator of a time-rescaled version of the process converges to the Laplace spectrum of the base manifold.

Wave Front Sets of Nilpotent Lie Group Representations - Weich, Tobias; Budde, Julia (arXiv:2103.02968v1)

Have Academics’ Citation Patterns Changed in Response to the Rise of World University Rankings? A Test Using First-Citation Speeds - Lee, Soo Jeung; Schneijderberg, Christian; Kim, Yangson; Steinhardt, Isabel (Sustainability)
Academics may actively respond to the expectations of the academic status market, which have largely been shaped by the World University Rankings (WURs). This study empirically examines how academics’ citation patterns have changed in response to the rise of an “evaluation environment” in academia. We regard the WURs to be a macro-level trigger for cementing a bibliometric-based evaluation environment in academia. Our analyses of citation patterns in papers published in two higher education journals explicitly considered three distinct periods: the pre-WURs (1990–2003), the period of WURs implementation (2004–2010), and the period of adaption to WURs (2011–2017). We applied the nonparametric Kaplan–Meier method to compare first-citation speeds of papers published across the three periods. We found that not only has first-citation speed become faster, but first-citation probability has also increased following the emergence of the WURs. Applying Cox proportional hazard models to first-citation probabilities, we identified journal impact factors and third-party funding as factors influencing first-citation probability, while other author- and paper-related factors showed limited effects. We also found that the general effects of different factors on first-citation speeds have changed with the emergence of the WURs. The findings expand our understanding of the citation patterns of academics in the rise of WURs and provide practical grounds for research policy as well as higher education policy.
Keywords: world university rankings; citation; first-citation speed; Minerva; Studies in Higher Education

ASSET: A Semi-supervised Approach for Entity Typing in Knowledge Graphs - Zahera, Hamada Mohamed Abdelsamee; Heindorf, Stefan; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th on Knowledge Capture Conference)

Drift Detection in Text Data with Document Embeddings - Feldhans, Robert; Wilke, Adrian; Heindorf, Stefan; Shaker, Mohammad Hossein; Hammer, Barbara; Ngonga Ngomo, Axel-Cyrille; Hüllermeier, Eyke (Intelligent Data Engineering and Automated Learning – IDEAL 2021)

Convolutional Hypercomplex Embeddings for Link Prediction - Demir, Caglar; Moussallem, Diego; Heindorf, Stefan; Ngonga Ngomo, Axel-Cyrille (The 13th Asian Conference on Machine Learning, ACML 2021)
Knowledge graph embedding research has mainly focused on the two smallest normed division algebras, $\mathbb{R}$ and $\mathbb{C}$. Recent results suggest that trilinear products of quaternion-valued embeddings can be a more effective means to tackle link prediction. In addition, models based on convolutions on real-valued embeddings often yield state-of-the-art results for link prediction. In this paper, we investigate a composition of convolution operations with hypercomplex multiplications. We propose the four approaches QMult, OMult, ConvQ and ConvO to tackle the link prediction problem. QMult and OMult can be considered as quaternion and octonion extensions of previous state-of-the-art approaches, including DistMult and ComplEx. ConvQ and ConvO build upon QMult and OMult by including convolution operations in a way inspired by the residual learning framework. We evaluated our approaches on seven link prediction datasets including WN18RR, FB15K-237 and YAGO3-10. Experimental results suggest that the benefits of learning hypercomplex-valued vector representations become more apparent as the size and complexity of the knowledge graph grows. ConvO outperforms state-of-the-art approaches on FB15K-237 in MRR, Hit@1 and Hit@3, while QMult, OMult, ConvQ and ConvO outperform state-of-the-approaches on YAGO3-10 in all metrics. Results also suggest that link prediction performances can be further improved via prediction averaging. To foster reproducible research, we provide an open-source implementation of approaches, including training and evaluation scripts as well as pretrained models.

Generating Physically Sound Training Data for Image Recognition of Additively Manufactured Parts - Nickchen, Tobias; Heindorf, Stefan; Engels, Gregor (2021 IEEE Winter Conference on Applications of Computer Vision (WACV))

Automatically generating instructions from tutorials for search and user navigation - Heindorf, Stefan

Integrated superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Verma, Varun B; Protte, Maximilian; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Ebers, Lena; Hammer, Manfred; Förstner, Jens; Silberhorn, Christine; Mirin, Richard P; Woo Nam, Sae; et al. (Journal of Physics: Photonics)
We demonstrate the integration of amorphous tungsten silicide superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides. We show proof-of-principle detection of evanescently coupled photons of 1550 nm wavelength using bidirectional waveguide coupling for two orthogonal polarization directions. We investigate the internal detection efficiency as well as detector absorption using coupling-independent characterization measurements. Furthermore, we describe strategies to improve the yield and efficiency of these devices.

A Multi-Model-Particle Filtering-Based Prognostic Approach to Consider Uncertainties in RUL Predictions - Bender, Amelie (Machines)
While increasing digitalization enables multiple advantages for a reliable operation of technical systems, a remaining challenge in the context of condition monitoring is seen in suitable consideration of uncertainties affecting the monitored system. Therefore, a suitable prognostic approach to predict the remaining useful lifetime of complex technical systems is required. To handle different kinds of uncertainties, a novel Multi-Model-Particle Filtering-based prognostic approach is developed and evaluated by the use case of rubber-metal-elements. These elements are maintained preventively due to the strong influence of uncertainties on their behavior. In this paper, two measurement quantities are compared concerning their ability to establish a prediction of the remaining useful lifetime of the monitored elements and the influence of present uncertainties. Based on three performance indices, the results are evaluated. A comparison with predictions of a classical Particle Filter underlines the superiority of the developed Multi-Model-Particle Filter. Finally, the value of the developed method for enabling condition monitoring of technical systems related to uncertainties is given exemplary by a comparison between the preventive and the predictive maintenance strategy for the use case.
Keywords: prognostics; RUL predictions; particle filter; uncertainty consideration; Multi-Model-Particle Filter; model-based approach; rubber-metal-elements; predictive maintenance